Penguatan Orientasi Perguruan Tinggi Berbasis Agro-Marine Industry Melalui Sosialisasi pada Siswa-Siswi SMA Negeri 1 Samatiga Kabupaten Aceh Barat - Wahyuningsih, Yayuk Eko; Husen, Tamitha Intassar; Damrus, Damrus; Ansari, Leli Putri; Ariani, Dian; Trisna, Nila (Universitas Teuku Umar, 2025)
The progress of a country is inseparable from the stability of its human resources. A greater effort is needed in various fields, especially in education. This service aims to provide an understanding of campus selection for further studies that align with Indonesia's potential as an agrarian and maritime country. The activity is conducted every March each year for high school students on the southwestern coast of Aceh province, and currently for the 9th-grade students of SMA Negeri 1 Samatiga. The method used includes lectures, question and answer sessions, and watching videos divided into three stages: introduction, implementation, and monitoring and evaluation. The results of the community service show that students have an interest in continuing to higher education but are hindered by costs. Therefore, Teuku Umar University can be a solution due to its relatively close distance and affordable fees, with the hope that they will succeed in the future